An evidence for prompt electric field disturbance driven by changes in the solar wind density under northward IMF Bz condition. Issue 5 (26th May 2016) - Rout, Diptiranjan; Chakrabarty, D.; Sekar, R.; Reeves, G. D.; Ruohoniemi, J. M.; Pant, Tarun K.; Veenadhari, B.; Shiokawa, K.
Abstract: Before the onset of a geomagnetic storm on 22 January 2012 ( A p = 24), an enhancement in solar wind number density from 10/cm 3 to 22/cm 3 during 0440–0510 UT under northward interplanetary magnetic field (IMF B z ) condition is shown to have enhanced the high‐latitude ionospheric convection and also caused variations in the geomagnetic field globally. Conspicuous changes in Δ X are observed not only at longitudinally separated low‐latitude stations over Indian (prenoon), South American (midnight), Japanese (afternoon), Pacific (afternoon) and African (morning) sectors but also at latitudinally separated stations located over high and middle latitudes. The latitudinal variation of the amplitude of the Δ X during 0440–0510 UT is shown to be consistent with the characteristics of prompt penetration electric field disturbances. Most importantly, the density pulse event caused enhancements in the equatorial electrojet strength and the peak height of the F layer ( h m F 2 ) over the Indian dip equatorial sector. Further, the concomitant enhancements in electrojet current and F layer movement over the dip equator observed during this space weather event suggest a common driver of prompt electric field disturbance at this time. Such simultaneous variations are found to be absent during magnetically quiet days. In absence of significant change in solar wind velocity and magnetospheric substorm activity, these observations point toward perceptible prompt electric field disturbance over the dip equator driven by the overcompression of the magnetosphere by solar wind density enhancement. Key Points: Prompt penetration electric field driven by solar wind density Equatorial electric field disturbance under northward IMF Bz Signatures in global magnetic data and geosynchronous count rate